2020
DOI: 10.1016/j.vetmic.2020.108604
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of orally administered porcine epidemic diarrhea vaccine-loaded hydroxypropyl methylcellulose phthalate microspheres and RANKL-secreting L. lactis

Abstract: Here, we examined the efficacy of are combinant subunit antigen-based oral vaccine for preventing porcine epidemic diarrhea virus (PEDV). First, we generated a soluble recombinant partial spike S1 protein (aP2) from PEDV in E. coli and then evaluated the utility of aP2 subunit vaccine-loaded hydroxypropyl methylcellulose phthalate microspheres (HPMCP) and RANKL-secreting L. lactis (LLRANKL) as a candidate oral vaccine in pregnant sows. Pregnant sows were vaccinated twice (with a 2 week interval between doses) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In addition, a significant positive effect on average daily weight gain (between 44 and 59 g/day) in the finishing phase was observed from pigs administered with the PCV2 vaccine via the ID route [4]. The survival rate after challenge of newborn suckling piglets delivered by sows vaccinated with ID PED vaccine in this study was similar to that of piglets delivered by sows vaccinated with PED aP2 subunit vaccine (loaded hydroxypropyl methylcellulose phthalate microspheres plus RANKL-secreting L. lactis) [33].…”
Section: Discussionsupporting
confidence: 64%
“…In addition, a significant positive effect on average daily weight gain (between 44 and 59 g/day) in the finishing phase was observed from pigs administered with the PCV2 vaccine via the ID route [4]. The survival rate after challenge of newborn suckling piglets delivered by sows vaccinated with ID PED vaccine in this study was similar to that of piglets delivered by sows vaccinated with PED aP2 subunit vaccine (loaded hydroxypropyl methylcellulose phthalate microspheres plus RANKL-secreting L. lactis) [33].…”
Section: Discussionsupporting
confidence: 64%
“…In the study by Makadiya et al maximum titers of approximately 90 (unconverted titer) are reported after injection of purified recombinant protein (Makadiya et al 2016). In a more recent report (Choe et al 2020), a similar neutralizing antibody titer of 7-8 on a log 2 scale was obtained on oral immunization with S1-containing microspheres. The work presented here indicates that the orally-delivered S1 produced in maize can elicit a response similar to other subunit vaccine delivery systems.…”
Section: Discussionmentioning
confidence: 78%
“…At present, two strategies have been used to induce mucosal immunity. The first one involves applying suitable carriers for delivering vaccines by mucosal routes; a whole PEDV attenuated strain entrapped in the enteric material hydroxypropyl methyl cellulose phthalate (HPMCP) successfully induced both mucosal immunity and systemic immunity after oral immunization in weaned piglets [ 181 , 182 ]. PEDV killed vaccine antigens (KAg) entrapped in PLGA particles was delivered intranasally to sows at 28 and 14 days prior to farrowing.…”
Section: Discussionmentioning
confidence: 99%